1997
DOI: 10.1002/masy.19971220138
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of polycondensation in an industrial environment

Abstract: The influence of industrial reaction conditions on the kinetics of the polycondensation of polyamides is discussed. For analysis reasons the overall process was subdivided into individual kinetic phases. It will be shown that the basic features of the reaction rate in the final reaction stage can be explained assuming second order kinetics combined with a superposed reaction equilibrium. The influence of non‐stoechiometry on the reaction rate is also demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 3 publications
2
12
0
1
Order By: Relevance
“…The activation energies are very similar for all the samples, with an average value of 67 kJ/mol. This value substantially agrees with the value of 62.2 kJ/mol reported for the second-order kinetic constant of a similar polyamide by Blondel et al 9 This is further confirmation that t x is a good characteristic kinetic parameter for following the postcondensation kinetics of nylon. In addition, the activation energy does not depend on the initial moisture consent.…”
Section: Effect Of the Initial Moisture Content And Temperaturesupporting
confidence: 91%
See 1 more Smart Citation
“…The activation energies are very similar for all the samples, with an average value of 67 kJ/mol. This value substantially agrees with the value of 62.2 kJ/mol reported for the second-order kinetic constant of a similar polyamide by Blondel et al 9 This is further confirmation that t x is a good characteristic kinetic parameter for following the postcondensation kinetics of nylon. In addition, the activation energy does not depend on the initial moisture consent.…”
Section: Effect Of the Initial Moisture Content And Temperaturesupporting
confidence: 91%
“…Normally, second-order kinetics (first-order in both amine and acid groups) describe satisfactorily the polycondensation of PA11 in the melt phase. 8,9 Variations in the melt viscosity can therefore be used to monitor changes in the molecular weight. In particular, second-order kinetics lead to single exponential growth for the viscosity.…”
Section: Evolution Of the Linear Viscoelastic Propertiesmentioning
confidence: 99%
“…As shown in Table 7 , they used these data to estimate 20 kinetic parameters (including 10 activation energies) and 10 equilibrium parameters (including 5 reaction enthalpies). Parameter values estimated by other research groups (using smaller data sets or unpublished data) are also shown in Table 7 11,14–16,18,24,25,32,35,42,45–547 are similar for different research groups (e.g., the activation energy estimate of 78.7 kJ mol −1 for R1 reported by Arai et al11 is similar to 78.5 kJ mol −1 reported by Reimschussel et al,45 other parameter estimates differ by orders of magnitude between research groups.…”
Section: Reaction Mechanism and Literature Reviewsupporting
confidence: 62%
“…Para meter values estimated by other research groups (using smaller data sets or unpublished data) are also shown in Table 7. [11,[14][15][16]18,24,25,32,35,42,[45][46][47][48][49][50][51][52][53][54] Although some of the para meter values in Table 7 are similar for different research groups (e.g., the activation energy estimate of 78.7 kJ mol −1 for R1 reported by Arai et al [11] is similar to 78.5 kJ mol −1 reported by Reimschussel et al, [45] other parameter esti mates differ by orders of magnitude between research groups.…”
Section: Reaction Mechanism and Literature Reviewmentioning
confidence: 65%
“…Mixtures of 11-aminoundecanoic acid and 11-heptylaminoundecanoic acid with, respectively, 0, 1 and 5 wt% of 11-eptylaminoundecanoic were employed for the syntheses, no catalyst was used in order to increase the thermal stability of the produced polymers and hence to enlarge the time window available for further rheological tests. Details about the polycondensation conditions can be found elsewhere [31]. The produced polyamides will be denoted further on in this paper as linear PA11, 1% C7 and 5% C7 in memory of the weight percentage of heptylaminoundecanoic used for the synthesis.…”
Section: Methodsmentioning
confidence: 99%